Experimental investigation of flow-induced sound of kite lines - Saur, Lukas; Riedel, Jörg; Dunker, Storm; Becker, Stefan (Acta Acustica, 2023)
In times of increasing importance of renewable energies, airborne wind energy (AWE) systems represent an emerging extension to conventional wind turbines. Many AWE systems use powerful kites to provide tether traction to mechanically unwind the tether, generating electricity on the ground. In addition to the traction tether, a large number of kite lines spanning the kite are moved through the air at high speed. This can produce a loud unpleasant whistling noise on the ground, which is due to a superposition of the aeolian tones of the many different lines. In the present work, differently structured kite lines were investigated in the aeroacoustic wind tunnel with respect to their sound radiation when they were exposed to a flow at up to 34 ms-1 resulting in Re ¦ 7300 and angles of attack (AOA) in the range of 90 § AOA § 45. It was found that greater surface roughness increases sound radiation while line tension has negligible influence. By weaving a single-helix-shaped protrusion into the sheath of the kite line, the total radiated sound pressure level can be reduced by up to 9 dB. If the line itself has a helical contour, even a reduction of up to 11.5 dB is reachable. For decreasing AOA the noise suppression effect of helical surface protrusions and helical line shape is significantly reduced. The results provide initial guidelines on how to effectively reduce sound radiation from aircraft kites. Further investigations should consider the individual contributions of fluid and structural sounds to the total radiated sound of a flying kite.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Flow-induced noise; Helical surface protrusions; Kite lines; Noise control; Strouhal frequency